2017
DOI: 10.1016/j.seares.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Variation that can be expected when using particle tracking models in connectivity studies

Abstract: Hydrodynamic Ocean Circulation Models and Lagrangian particle tracking models are valuable tools e.g. in coastal ecology to identify the connectivity between offshore spawning and coastal nursery areas of commercially important fish, for risk assessment and more for defining or evaluating marine protected areas. Most studies are based on only one model and do not provide levels of uncertainty. Here this uncertainty was addressed by applying a suite of 11 North Sea models to test what variability can be expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…A further reason that may have led to the noncorrelation of estimated migration rates and modelled number of arriving particles could be that the particle arrival rates between sampling locations did not represent the actual hydrodynamic processes, which are underlying the exchange of larvae between these locations. Accordingly, comparison studies revealed large variations between different PTMs (Hufnagl et al, ). Particle models are driven by hydrodynamic models that are driven by meteorological forcing, which may influence tidal movements and residual currents in the North Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further reason that may have led to the noncorrelation of estimated migration rates and modelled number of arriving particles could be that the particle arrival rates between sampling locations did not represent the actual hydrodynamic processes, which are underlying the exchange of larvae between these locations. Accordingly, comparison studies revealed large variations between different PTMs (Hufnagl et al, ). Particle models are driven by hydrodynamic models that are driven by meteorological forcing, which may influence tidal movements and residual currents in the North Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, comparison studies revealed large variations between different PTMs (Hufnagl et al, 2016). Particle models are driven by hydrodynamic models that are driven by meteorological forcing, which may influence tidal movements and residual currents in the Furthermore, many sample combinations were not connected according to the PTMs, resulting in many zeros in the arriving particles matrix.…”
Section: Mussels Have Been Transported Historically Between the Waddenmentioning
confidence: 99%
“…However, also Eulerian surface currents used can be a ma-jor source of uncertainty (Hufnagl et al, 2017). The circulation model BSHcmod, which this study mainly focuses on, is run operationally.…”
Section: Introductionmentioning
confidence: 99%
“…Corell et al, ; Paris, Chérubin, & Cowen, 2007), and also possible settling behaviour. The combination of oceanographic circulation models with individual‐based particle tracking models including relevant biological traits is considered a valuable approach to estimate connectivity in the seascape (Cowen & Sponaugle, ; Hufnagl et al, ; Paris, Chérubin, & Cowen, ). Several studies also show that connectivity estimated from biophysical models can explain significant variation in population structure revealed by genetic markers (Buonomo et al, ; Jahnke et al, ; Selkoe et al, ).…”
Section: Discussionmentioning
confidence: 99%